Perceptions and Preferences of Pharmacy Students Towards Classroom Based Versus Online Teaching-Learning and Assessment: A Survey During Covid Pandemic: Pharmaceutical Science-Pharmacy Education - Ravikumar, Chandini; Roupal Morais, Shabna; Nagasubramanian, Vanitha Rani (International Journal of Life Science and Pharma Research, 2022)
This study aimed to assess the perception and the preferences of undergraduate pharmacy students towards traditional classroom-based versus online teaching-learning and assessment during the COVID-19 pandemic. A standardized questionnaire was developed, statistically validated and administered to a total of 531 students pursuing Pharm. D or B. Pharm in the Pharmacy college of a deemed university through mail and WhatsApp as google forms. The completed responses obtained from 454 students were analyzed for their preferences and perceptions towards both methods of teaching-learning and assessments. The significant differences in the responses between students of both programs were assessed using unpaired sample t-test. There were 288 (64%) responses from B. Pharm and 166 (36%) from Pharm. D students. The difference in year of study (i.e. duration of the program), age and number of courses between the two programs were highly significant. Majority of the students stated classroom-based teaching as more advantageous (42.6%). Easy access to the teaching material (51.4%) and lack of personal contact with the teacher (40.2%) were considered as major advantage and disadvantage to online teaching-learning respectively. 54.1% of students opted for online and 46.9% chose traditional classroom teaching for interest generation towards learning. Majority of the students in both programs (43% and 53% respectively) preferred both classroom-based and online teaching-learning to enhance their knowledge, skills and self-directed learning. Similarly, the preferences for assessments were higher for conventional mode of in-person written examinations (71.2%) and remote online assessments (29.8%) through multiple choice questions, assignments etc. Thus students’ perception towards an in depth understanding of the concepts was in favour of traditional classroom based teaching learning, whereas interest towards learning and accessibility to study materials were in favour of online teaching learning. Most of the students preferred learning through blended mode rather than being exposed to either one of the teaching-learning techniques. However, there was a higher preference for conventional in-person mode than the online mode of assessments. Academic dishonesty, technological inconsistency and incompetency were identified as major bottlenecks for remote online assessments.